2021
DOI: 10.3389/fimmu.2021.755623
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Monocytes Are Prone to Migrate Into Tumor in Diffuse Large B-Cell Lymphoma

Abstract: Absolute count of circulating monocytes has been proposed as an independent prognostic factor in diffuse large B-cell lymphoma (DLBCL). However, monocyte nomenclature includes various subsets with pro-, anti-inflammatory, or suppressive functions, and their clinical relevance in DLBCL has been poorly explored. Herein, we broadly assessed circulating monocyte heterogeneity in 91 DLBCL patients. Classical- (cMO, CD14pos CD16neg) and intermediate- (iMO, CD14pos CD16pos) monocytes accumulated in DLBCL peripheral b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
3
2
Order By: Relevance
“…4 D). However, it was reported that cMO and iMO were enriched in the peripheral blood of DLBCL patients, whereas the abundance of ncMO should be lower [ 15 ], which was not consistent with our analysis results. To explore the reason, we further analyzed the two ncMO cell subsets and found that the ratio of the ncMO1 subset was in line with the previous report, whereas another subset, ncMO2, was significantly higher in the DHL and DLBCL groups than that in the healthy group (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…4 D). However, it was reported that cMO and iMO were enriched in the peripheral blood of DLBCL patients, whereas the abundance of ncMO should be lower [ 15 ], which was not consistent with our analysis results. To explore the reason, we further analyzed the two ncMO cell subsets and found that the ratio of the ncMO1 subset was in line with the previous report, whereas another subset, ncMO2, was significantly higher in the DHL and DLBCL groups than that in the healthy group (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…As regards to monocytes, research has shown that classic monocytes are important for the initial inflammatory response, while non-classical monocytes are widely believed to have anti-inflammatory effects [ 35 , 36 ]. In this analysis, we found a non-classical monocyte subset inconsistent with existing reports [ 15 ], namely the ncMO2 cell subset, which was abnormally and significantly elevated in patient samples. For this subpopulation, we delved into the expression of its surface antigens, and most of the antibody markers we used (including CD45RA and CD45RO) showed higher levels than that in the other subpopulation (ncMO1).…”
Section: Discussioncontrasting
confidence: 99%
“…An increased number of circulating CD16 pos ncMo, which display a combined inflammatory/tolerogenic phenotype and can be recruited by tumor B cells, has been shown in DLBCL. 73 All these observations suggest an increased recruitment of monocytes, including ncMo, to the tumor in DLBCL, in which the ANXA1-FPR interaction could be a key player in the monocyte-derived TAM infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, Rusak et al [115] developed a marker panel for B cells (CD19 + , CD20 + , CD22 + , and CD79a + ), T cells (CD3 + /CD4 + /CD5 + /CD8 + ), and Treg cells (CD4 + /CD25 +++ /Foxp3 high ) to determine their absolute counts and correlate such information for the prognostication of newly diagnosed DLBCL patients. They have also suggested the usage of monocytic population distribution in DLBCL patients as an independent prognostic factor [116]. Thus, a greater number of classical (cMo, CD14 + /CD16 − ) and intermediate monocytes (iMo, CD14 + /CD16 + ), and a decrease in the non-classical counterpart (ncMo, CD14 low /CD16 + ) were detected in the PB of patients with favorable prognosis.…”
Section: Proteomics Studies On Diffuse Large B Cell Lymphoma (Dlbcl)mentioning
confidence: 97%
“…Finding differentially expressed proteins between FL and MCL [95] MCL Identification of molecular signatures that differentiate MCL from B cells of the different compartments [96] Identification of proteomic biomarkers to distinguish MCL [97] Searching for specific proteomic biomarkers overexpressed in MCL tumor biopsies [98] Identification of tyrosine-phosphorylated proteins [99] Provision of insights into the dynamics of the disease and response to treatment [99] Evaluation of resistance to antinucleoside drugs [100] Discovery of neo-antigen peptides that mediate the killing of autologous lymphoma cells by circulating CD4 T cells [101] Characterization of the action mechanism of the MDM2-antagonist nutlin-3a [102] Discovery of the mechanisms involved in the pathogenesis of ocular adnexa extranodal MZL [103] Identification of biomarkers for the diagnosis of primary Sjögren's syndrome/MALT and prediction of progression [104] Establishment of the role of ID3 in regulating cell proliferation [105] MZL Study of the pharmacokinetics of umbralisib [106] BL Analysis of differentially expressed proteins between endemic and sporadic BL variants and EBV + and EBV − BL cell lines [107] Prediction of MGUS progression for an early diagnosis of MM [108] Analysis of the tumor microenvironment to identify determinants of durable responses to BCMA CAR T therapy [109] Quantification of surface proteins to identify immunotherapy targets and biomarkers associated with resistance and response to treatment [109] MM Identification of cell surface targets for immune-based therapies [110] Flow Cytometry CLL Design of panels for rapid disease diagnosis and progression assessment [111,112] Comparison of residual normal B cell profiles between CLL and MBL [113] B-ALL Evaluation of neuropilin-1/CD304 as minimal residual disease and prognostic marker [114] DLBCL Assessment of the absolute counts of B cells, T cells, and Treg cells for the prognostication of newly diagnosed DLBCL patients [115] Evaluation of the monocytic population distribution as an independent prognostic factor [116] DLBCL & FL Usage of aneuploidy and cell cycle indexing as tools for differentiating between CD10 + DLBCL and FL [117] DLBCL & BL Identification of cell markers to differentiate between BL and CD10 + DLBCL [118] MZL Distinguishing IgG4-related ophthalmic disease, idiopathic orbital inflammatio...…”
Section: Discovery Of Predictive Indicators Of Histological Transform...mentioning
confidence: 99%